Analisis Kepuasan Pelanggan Homestay Syariah Desa Bahasa Borobudur: dengan Pendekatan Teori Tradisional Dimension - Khoiriyah, Siti; Purwanto; Labib, Achmad (ARBITRASE: Journal of Economics and Accounting, 2023)
The purpose of this study is to complete the literature on the factors that influence customer satisfaction at the Borobudur Language Village Syariah Homestay, which previously had not studied much Traditional Dimension theory. This research method uses qualitative research methods. The results of the study show that quality values, price values, emotional values ??and social values ??affect customer satisfaction in village sharia homestays. Borobudur language, traditional theory dimension. Customer satisfaction is the part that relates to the creation of customer value. Because the creation of customer satisfaction means providing benefits for the company, namely, including the relationship between the company and its customers to be harmonious, providing a good basis or creating customer satisfaction and forming a word of mouth recommendation that is profitable for the company, resulting in interest from customers to buy or use the company's services The traditional dimension theory is really relevant for testing customer satisfaction values ??at the sharia homestay of the Language Village in Borobudur.